2016
DOI: 10.1016/j.ijrobp.2016.06.760
|View full text |Cite
|
Sign up to set email alerts
|

Distant Brain Recurrence in Patients With 5 or More Newly Diagnosed Brain Metastases Treated With Stereotactic Radiosurgery (SRS) or Fractionated Stereotactic Radiation Therapy (FSRT) Alone

Abstract: Background To assess the clinical outcomes in patients with greater than 4 newly diagnosed brain metastases treated with focal stereotactic radiotherapy alone. Methods All patients with five or more brain metastases who received focal radiotherapy without whole brain radiation or resection were included in this retrospective analysis. Distant brain failure (DBF), overall survival (OS) and toxicity were reported. Results Thirty-six patients met inclusion with median clinical follow-up of 6.3 months (range: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Other factors must be considered, including histology, control of systemic disease, existing systemic therapy options, and predicted survival. 34,35 For example, Fiveash et al analyzed outcomes of SRS in patients with 5 or more brain metastases and demonstrated that neither tumor volume nor tumor number were predictive of distant failure in multivariate analysis. 35 Risk of distant brain failure in 6 months in our study was 58%, which is comparable to historical controls, where risk of distant brain failure in patients following SRS alone was similar and ranged from 35-64% 3,29,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors must be considered, including histology, control of systemic disease, existing systemic therapy options, and predicted survival. 34,35 For example, Fiveash et al analyzed outcomes of SRS in patients with 5 or more brain metastases and demonstrated that neither tumor volume nor tumor number were predictive of distant failure in multivariate analysis. 35 Risk of distant brain failure in 6 months in our study was 58%, which is comparable to historical controls, where risk of distant brain failure in patients following SRS alone was similar and ranged from 35-64% 3,29,35 .…”
Section: Discussionmentioning
confidence: 99%
“… 33 , 34 For example, Barrett et al 35 analyzed outcomes of SRS in patients with 5 or more brain metastases and demonstrated that neither tumor volume nor tumor number were predictive of distant failure in multivariate analysis. Risk of distant brain failure in 6 months in our study was 58%, which is comparable with historical controls, where risk of distant brain failure in patients after SRS alone was similar and ranged from 35% to 64% 3 , 28 , 35 In addition, Nam et al demonstrated no differences in distant brain failure between those who had 1 to 3 versus 4 to 10 brain metastases. 36 More than half of our patients did not experience a distant recurrence (21 of 40), and the cumulative incidence at 1 year for distant recurrence was 35.8%.…”
Section: Discussionmentioning
confidence: 99%